6(k+4)-(5+9k)=-4k

Simple and best practice solution for 6(k+4)-(5+9k)=-4k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(k+4)-(5+9k)=-4k equation:


Simplifying
6(k + 4) + -1(5 + 9k) = -4k

Reorder the terms:
6(4 + k) + -1(5 + 9k) = -4k
(4 * 6 + k * 6) + -1(5 + 9k) = -4k
(24 + 6k) + -1(5 + 9k) = -4k
24 + 6k + (5 * -1 + 9k * -1) = -4k
24 + 6k + (-5 + -9k) = -4k

Reorder the terms:
24 + -5 + 6k + -9k = -4k

Combine like terms: 24 + -5 = 19
19 + 6k + -9k = -4k

Combine like terms: 6k + -9k = -3k
19 + -3k = -4k

Solving
19 + -3k = -4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '4k' to each side of the equation.
19 + -3k + 4k = -4k + 4k

Combine like terms: -3k + 4k = 1k
19 + 1k = -4k + 4k

Combine like terms: -4k + 4k = 0
19 + 1k = 0

Add '-19' to each side of the equation.
19 + -19 + 1k = 0 + -19

Combine like terms: 19 + -19 = 0
0 + 1k = 0 + -19
1k = 0 + -19

Combine like terms: 0 + -19 = -19
1k = -19

Divide each side by '1'.
k = -19

Simplifying
k = -19

See similar equations:

| 7+5(1+2x)=-2(5+6x) | | 8(8x+4)=-32-7x | | 3x+2x+20x= | | 2y+4=-5 | | 15=-5(4-7x) | | 6(v+4)-2v=2(2v+2)-11 | | x-4x=2x+1-5x | | 3-0.5r=12 | | 6=-w/8 | | 3.4x-1.4=1.36-3.5x | | 3(2x-3)=6(x+1)-15 | | 21x-2=4(5x+3)-10 | | X+13=-14 | | .7x+.05(6-x)=.1(-88) | | |p-7|+13=5 | | s+2-3-16=0 | | 80=3x+19 | | 22+8x=-5+3(5x-5) | | -2(a-5)=27-2a | | 20(x-1)=-4(5-x)+16x | | y^2+11y-12=0 | | 12y^2-4y^4= | | 4x-2(x-7)=4 | | 6x^2+5x-8=-4 | | 43+63+57+4x=55 | | .18y+.04(y+6000)=1780 | | us+uz=t | | 7n=85n | | 2r-(-4+r)=7-2r | | 32y+5y=2 | | 6x-12+2x=7+8x-19 | | 7x+1x=3x+3 |

Equations solver categories